Smoking habit affects the qualities of stored leukodepleted red blood cells - Aulia Eka Sari Sari; Ni Ken Ritchie; Mohammad Sadikin (Indonesian Archives and Biomedical Sciences, 2021)
Background: Pack Red Cell (PRC) is one of the most widely used blood products. Indonesia has a high number of smokers who are potential donors. Smoking is a habit that can cause radicals, triggers oxidative stress so that transfusion becomes ineffective. Objective: This study aimed to determine the relationship between smoking habits and methemoglobin, glutathione, and glucose 6 phosphate dehydrogenase (G6PD) in leukodepleted PRC (PRC-LD) blood bags during storage. Methods: PRC-LD from the Jakarta Red Cross Transfusion Unit were grouped into non-smoker donors (NP), light smoker donors (PR), and moderate smoking donors (PS).  Analysis for methemoglobin, glutathione, and G6PD was performed on days 0, 14, 21, and 35h. The analysis was done spectrophotometrically. Results:  Statistical analysis indicates that methemoglobin was increased on days 21 and 35, glutathione levels decreased progressively on days 0, 14, 21, and 35. The G6PD activities decreased markedly on day 35 in all groups. A significant relationship was found between methemoglobin and glutathione, as well as G6PD and glutathione. Conclusion: Smoking habits make the storage blood condition worse.